2023
DOI: 10.3390/ijms241411801
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Extracellular Vesicles on Lung Stromal Cells during Breast Cancer Metastasis

Abstract: Breast cancer is a prominent cause of cancer diagnosis and death in women globally, with over 90% of deaths being attributed to complications that arise from metastasis. One of the common locations for breast cancer metastasis is the lung, which is associated with significant morbidity and mortality. Curative treatments for metastatic breast cancer patients are not available and the molecular mechanisms that underlie lung metastasis are not fully understood. In order to better treat these patients, identifying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 159 publications
0
2
0
Order By: Relevance
“…In order to improve the clinical detection of secondary lung cancers and to complement current imaging strategies, recent research efforts have led to the development of robust non-symptom-driven molecular screening assays. These assays have been designed to detect circulating primary tumor bioproducts such as circulating tumor cells (CTCs), circulating tumor DNA (ctDNA), circulating RNA transcripts (i.e., circular RNAs, messenger RNAs (mRNA), microRNAs (miRNA) and long non-coding RNAs), and more recently circulating tumor extracellular vesicles (EVs) [12][13][14][15][16][17][18] . Although the detection of CTCs has been used prognostically, it is not foolproof and a significant subset of patients who develop metastatic disease are not identified using this approach [19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the clinical detection of secondary lung cancers and to complement current imaging strategies, recent research efforts have led to the development of robust non-symptom-driven molecular screening assays. These assays have been designed to detect circulating primary tumor bioproducts such as circulating tumor cells (CTCs), circulating tumor DNA (ctDNA), circulating RNA transcripts (i.e., circular RNAs, messenger RNAs (mRNA), microRNAs (miRNA) and long non-coding RNAs), and more recently circulating tumor extracellular vesicles (EVs) [12][13][14][15][16][17][18] . Although the detection of CTCs has been used prognostically, it is not foolproof and a significant subset of patients who develop metastatic disease are not identified using this approach [19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, EVs may be used as reliable biomarkers for early cancer detection and cancer development [ 15 , 16 ]. There is growing evidence that tumor-derived EVs can promote angiogenesis by regulating the activity of endothelial cells at distant secondary sites to facilitate metastasis [ 17 ]. In this regard, EVs’ cargo may be associated with cancer progression; in fact, recent studies showed that EVs induce epithelial mesenchymal transition (EMT) via the modulation of Hippo tumor suppressor signaling pathway in breast cancer [ 18 ].…”
Section: Introductionmentioning
confidence: 99%